Implementing East Lombok Regency Regulation No. 2/2021 on Reducing Plastic Waste Generation through the INGES Waste Bank Program to Foster Ecological Citizenship - Rizka Aidiyatul Adha; Rispawati Rispawati; Basariah Basariah; Bagdawansyah Alqadri (Journal of Social and Humanities, 2025)
The problem of plastic waste is an environmental issue that requires addressing through public policy as a regulatory-based control instrument. This study aims to analyze the implementation of East Lombok Regency Regional Regulation Number 2 of 2021 concerning the limitation of plastic waste generation through the INGES Waste Bank Program in developing ecological citizens, and to identify the driving and inhibiting factors of its implementation. The study used a qualitative approach with a case study. Data collection was conducted through interviews, observation, and documentation. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Regional Regulation was carried out through four main programs: waste management socialization, a waste sorting movement from home, exchanging waste for WiFi vouchers, and processing waste into useful items. The implementation of these programs has resulted in increased environmental knowledge, environmental skills, environmental ethics, and environmental participation, reflecting the strengthening of ecological citizenship in the community. Driving factors for implementation include the existence of clear policy regulations and a strong commitment from the Dasan Lekong Village Government and the INGES Waste Bank management. Factors inhibiting implementation include budget limitations to support program facilities and infrastructure, practical lifestyles of people who maintain the use of single-use plastics, and unequal public awareness.